AB0089 Prevalence of metabolic syndrome in the moroccan population with rheumatoid arthritis: results from the quest-ra study. (23rd January 2014) - Bouazzaoui, L.; Rostom, S.; Benbrahim, L.; Benchekroun, B.; Ahid, S.; Bahiri, R.; Hajjaj-hassouni, N.
Abstract : Objectives: To evaluatethe prevalence of metabolic syndrome in patients with rheumatoid arthritis and analyze the factors that are associated with its presence. Methods: QUEST-RA Moroccan inspired by Finland QUEST-RA (Quantitative monitoring of standard patients with rheumatoid arthritis) is a multinational cross-sectional study, including patients with rheumatoid arthritis, according the criteria for diagnosis of ACR 1987, and collected in several Moroccan centers combining the public and private sector over a period of two years (from January 2008 to December 2010). A questionnaire containing sociodemographic, clinical and paraclinical parameters was completed by all patients. The definition of theWorld Health Organization (WHO 1998) was used to identify the metabolic syndrome. Metabolic syndrome is defined as the presence of at least two of the four following factors (obesity (BMI> 30 kg/m2), diabetes, hypertension, dyslipidemia). Results: 1129exploitable files were analyzed. The mean age of patients was 48.8 ± 12.7 years with female predominance 87.3%. The median disease duration was 6 years (3, 12), the mean DAS28 was 4.94 ± 1.68, with a median HAQ of1 (0.37, 1.62). The prevalence of hypertension, diabetes, hyperlipidemia, and obesity was respectively 13.7%, 8.3%, 4.4%, 17.6%. The prevalence of metabolic syndrome according to the WHO definition was 8.1%. In univariate analysis, the presence of metabolic syndrome was associated with a higher age of patients (p <0.0001) and a longer disease duration (p = 0.04) compared to the group without metabolic syndrome. In addition, there was no association between the presence of metabolic syndrome and DAS 28, ESR, CRP, The consumption of alcohol and tobacco, taking the dose of corticosteroids, the presence of bone erosions, anti-CCP and rheumatoid factor. Conclusions: This study suggeststhat there is no increased frequency of metabolic syndrome in rheumatoid arthritis in Morocco compared to literature data. The presence of metabolic syndrome was associated with age and disease duration of the disease unrelated to the activity or severity of the disease. Comparison with a control group and larger multiethnic studies are necessary. Disclosure of Interest: None Declared